2021
DOI: 10.3390/biom11101405
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Is Associated with a Lower Incidence of Benign Brain Tumors: A Retrospective Cohort Study in Patients with Type 2 Diabetes Mellitus

Abstract: Background: The risk of benign brain tumors (BBT) associated with metformin use has not received much attention. Therefore, a retrospective cohort study was designed to investigate such an association in patients with type 2 diabetes mellitus (T2DM). Methods: We used the database of Taiwan’s National Health Insurance to enroll 152,176 ever users and 16,120 never users of metformin for the follow-up of incidence of BBT and a more specific outcome of cerebral meningioma. The patients were newly diagnosed with T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although numerous studies have explored the relationship between metformin and tumors, there seems to be a scarcity of research on benign brain tumors such as meningiomas. A retrospective cohort study investigated the relationship between metformin and benign brain tumors (BBT) and revealed that metformin use reduced the risk of BBT, especially meningiomas, in patients with T2DM ( Tseng, 2021 ). Clinically, there are significantly more female patients with meningioma than male patients, with the ratio ranging from 2 to 3:1 ( Claus et al, 2005 ; Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have explored the relationship between metformin and tumors, there seems to be a scarcity of research on benign brain tumors such as meningiomas. A retrospective cohort study investigated the relationship between metformin and benign brain tumors (BBT) and revealed that metformin use reduced the risk of BBT, especially meningiomas, in patients with T2DM ( Tseng, 2021 ). Clinically, there are significantly more female patients with meningioma than male patients, with the ratio ranging from 2 to 3:1 ( Claus et al, 2005 ; Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have explored the relationship between metformin and tumors, there seems to be a scarcity of research on benign brain tumors such as meningiomas. A retrospective cohort study investigated the relationship between metformin and benign brain tumors (BBT) and revealed that metformin use reduced the risk of BBT, especially meningiomas, in patients with T2DM (Tseng, 2021). Clinically, there are significantly more female patients with meningioma than male patients, with the ratio ranging from 2 to 3:1 (Claus et al, 2005;Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have explored the relationship between metformin and tumors, there seems to be a scarcity of research on benign brain tumors such as meningiomas. A retrospective cohort study investigated the relationship between metformin and benign brain tumors (BBT) and revealed that metformin use reduced the risk of BBT, especially meningiomas, in patients with T2DM (Tseng, 2021). Clinically, there are significantly more female patients with meningioma than male patients, with the ratio ranging from 2 to 3:1 (Claus et al, 2005;Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%